The YfkO Nitroreductase from Bacillus Licheniformis on Gold-Coated Superparamagnetic Nanoparticles: Towards a Novel Directed Enzyme Prodrug Therapy Approach - Patrick Ball; Robert Hobbs; Simon Anderson; Emma Thompson; Vanessa Gwenin; Christopher Von Ruhland; Christopher Gwenin (MDPI AG, 2021)
The bacterial nitroreductase NfnB has been the focus of a great deal of research for its use in directed enzyme prodrug therapy in combination with the nitroreductase prodrug CB1954 with this combination of enzyme and prodrug even entering clinical trials. Despite some promising results, there are major limitations to this research, such as the fact that the lowest reported Km for this enzyme far exceeds the maximum dosage of CB1954. Due to these limitations, new enzymes are now being investigated for their potential use in directed enzyme prodrug therapy. One such enzyme that has proved promising is the YfkO nitroreductase from Bacillus Licheniformis. Upon investigation, the YfkO nitroreductase was shown to have a much lower Km (below the maximum dosage) than that of NfnB as well as the fact that when reacting with the prodrug it produces a much more favourable ratio of enzymatic products than NfnB, forming more of the desired 4-hydroxylamine derivative of CB1954.